TEORI-TEORI SOSIOLOGI AGAMA (EVOLUSI AGAMA, FAKTA SOSIAL, KAPITALISME, ALIENASI AGAMA) - kamila, faiza (Maliki Interdisciplinary Journal, 2025)
Religion has social and spiritual purposes and religion is also an important aspect of human life. Although religion has a spiritual purpose to fulfill the practical needs of humans, its social role is to create harmony among social groups and communities. Religion is universally the most fundamental component of human existence. Religion also provides meaning and purpose to human life, and also serves as a source of values, ethics, and morality. Religion and society interact with each other to influence life. There are many theories about the sociology of religion put forward by sociologists which will be discussed and described in this article. This article aims to provide a broad understanding of how the theory of the sociology of religion explains the relationship between religion, society, and social change by combining these various perspectives. There are several main theories in the sociology of religion which are certainly used to understand the social relationship between society and religion. In general, these theories are divided into three parts, namely classical theory, modern theory, and post-modern theory.